Recovery College influences upon service users: a Recovery Academy exploration of employment and service use. Issue 3 (22nd March 2019) - Sutton, Rebecca; Lawrence, Kate; Zabel, Elisabeth; French, Paul
Abstract : Purpose: The purpose of this paper is to provide an exploration of Recovery Academy influences upon employment and service use amongst individuals with lived experience of mental health difficulties. Design/methodology/approach: The study utilised a questionnaire design over a nine-month period. Participants' baseline and follow-up data were analysed to explore the influence of course attendance upon employment and service use. Findings: At follow-up, there was a significant association between participants attending Recovery Academy courses and paid or self-employment ( p <0.05). However, there were also no significant differences in service use over time between those who attended courses and those who did not attend any courses. Research limitations/implications: Further research is required to explore the cost-effectiveness of the Recovery Academy. As participants were all enroled onto the Recovery Academy findings may not be generalisable to other Recovery Colleges. There is a need for more robust research such as a randomised controlled trial (RCT) to evaluate multiple Recovery Colleges and establish definitive conclusions as to their economic implications. Social implications: There may be value in the Recovery Academy as a gateway to employment, speaking to the transformative powers of Recovery Colleges. The Recovery Academy may serve as a vehicle to support service users to obtain paid or self-employment, and thus promote community reintegration. Originality/value: This paper offers an important contribution to the Recovery College literature, which remains limited in evaluative evidence, particularly regarding associated economic factors, such as employment and service use.